A porcine large animal model of radiofrequency ablation-induced left bundle branch block - Wiedmann, Felix; Jamros, Max; Herlt, Valerie; Paasche, Amelie; Kraft, Manuel; Beck, Moritz; Prüser, Merten; Erkal, Atilla; Harder, Maren; Zaradzki, Marcin; Soethoff, Jasmin; Karck, Matthias; et al. (Frontiers in Physiology, 2024)
Background: Electrocardiographic (ECG) features of left bundle branch (LBB) block (LBBB) can be observed in up to 20-30 % of patients suffering from heart failure with reduced ejection fraction. However, predicting which LBBB patients will benefit from cardiac resynchronization therapy (CRT) or conduction system pacing remains challenging. This study aimed to establish a translational model of LBBB to enhance our understanding of its pathophysiology and improve therapeutic approaches.Methods: Fourteen male pigs underwent radiofrequency catheter ablation of the proximal LBB under fluoroscopy and ECG guidance. Comprehensive clinical assessments (12-lead ECG, bloodsampling, echocardiography, electroanatomical mapping) were conducted before LBBB induction, after 7 d, and 21 d. Three pigs received CRT pacemakers 7 d after LBB ablation to assess resynchronization feasibility.Results: Following proximal LBB ablation, ECGs displayed characteristic LBBB features, including QRS widening, slurring in left lateral leads, and QRS axis changes. QRS duration increased from 64.2±4.2 ms to 86.6±12.1 ms, and R wave peak time in V6 extended from 21.3±3.6 ms to 45.7±12.6 ms. Echocardiography confirmed cardiac electromechanical dyssynchrony, with septal flash appearance, prolonged septal-to-posterior-wall motion delay, and extended ventricular electromechanical delays. Electroanatomical mapping revealed a left ventricular breakthrough site shift and significantly prolonged left ventricular activation times. RF-induced LBBB persisted for three weeks. CRT reduced QRS duration to 75.9±8.6 ms, demonstrating successful resynchronization.This porcine model accurately replicates the electrical and electromechanical characteristics of LBBB observed in patients. It provides a practical, cost-effective, and reproducible platform to investigate molecular and translational aspects of cardiac electromechanical dyssynchrony in a controlled and clinically relevant setting.